Green Marketing: An Analysis of Consumer’s Perception and Willingness to Pay - Vivek, M C; Sahana, S. (Indian Journal of Extension Education, 2021)
There has been a gush in the usage of the term â€˜Greenâ€™, since people worldwide is becomingÂ more concerned about their environment. Green marketing is an emerging strategy which encompasses the marketing of the products that are assumed to be environmentally safe.Â Rising environmental concern has persuaded consumers and manufacturers towards green marketing. This paper attempts to study the environmental orientation of the young Indian consumer and their perception about green marketing. Primary data collected from 100Â consumers with the help of an online questionnaire was used for the study. The results revealed that consumers were having a high orientation towards the environment and theÂ majority preferred green products over conventional products. More than half of theÂ respondent consumers were willing to pay an additional 2-5 per cent of their actual price in case of green products. Consumers need to be made more aware about the issues thatÂ the product attempts to address. Green marketing should not be thought of as another approach for making profit. Rather it should be trailed with vigour, because of its ecological and social dimension.